Using the hedonic property method to value federal lands proximate to urban areas: a case study of Colorado Springs, Colorado - Ham, Charlotte, author; Loomis, John B., advisor; Reich, Robin M., committee member; Seidl, Andy, committee member; Goldstein, Joshua H., committee member; Champ, Patricia A., committee member (Colorado State University. Libraries, 2011)
Federal lands provide public benefits in many forms from consumptive to passive use. This dissertation explores the relationship between housing prices and federal land proximity to determine if there are property price effects for homes in close proximity to federal lands by using multiple spatial econometric techniques and model specifications for estimating hedonic pricing functions. First, relative economic values are estimated for public open spaces in El Paso County, Colorado. Then, the sensitivity of the estimated marginal values of proximity to federal lands is examined by varying the scale of the analysis from global (ordinary least squares) to local (geographically weighted). Finally, marginal values for the characteristics of the land uses on a federal land are calculated to determine if homeowner's value alternate land uses differently. The results show that multiple scales of analysis and model specifications should be explored when evaluating natural resource trade-offs because marginal values for environmental amenities vary across the landscape.
Keywords: hedonic property; willingness to pay; open space; land use; heterogeneity